Determination of 18 Trace Elements in 10 Batches of the Tibetan Medicine Qishiwei Zhenzhu Pills by Direct Inductively Coupled Plasma-Mass Spectrometry. (13th January 2022) - Fu, Ke; Song, Yinglian; Zhang, Dewei; Xu, Min; Wu, Ruixia; Xiong, Xueqing; Liu, Xianwu; Wu, Lei; Guo, Ya; Zhou, You; Li, Xiaoli; Wang, Zhang
Abstract : Qishiwei Zhenzhu pills (QSW) was first recorded in the Tibetan medicine classic Si Bu Yi Dian and has been used to treat "Baimai" disease, stroke, paralysis, hemiplegia, cerebral hemorrhage, and other diseases till today. This prescription contains more than 70 medicines including myrobalan, pearl, agate, opal, bezoar, coral, musk, gold, silver, and a mineral mixture Zuotai. As a result, QSW contains a large amount of mercury, copper, lead, and other trace elements. The aim of this study was to determine the 18 trace elements (lithium, beryllium, scandium, vanadium, chromium, manganese, cobalt, nickel, copper, arsenic, strontium, argentum, cadmium, cesium, barium, lead, aurum, and mercury) in 10 batches of QSW produced by 5 pharmaceutical companies (Ganlu Tibetan Medicine Co., Ltd. has 6 different batches) by direct inductively coupled plasma-mass spectrometry (ICP-MS). ICP-MS is a rapid, sensitive, accurate methodology allowing the determination of 18 elements simultaneously. The results showed that each element had an excellent linear relationship in the corresponding mass concentration range. The results showed that the rank order of the elements in QSW was copper > mercury > lead from high to low, with the mass fraction higher than 6000  μ g/kg; the mass fractions of argentum, arsenic, manganese, aurum, strontium, barium, chromium, and nickel were in the range of 33–1034  μ g/kg; and the mass fractions of vanadium, cobalt, lithium, beryllium, cadmium, scandium, and cesium were lower than 10  μ g/kg. The reproducibility from the same manufacturer (Tibet Ganlu Tibetan Medicine Co., Ltd.) was relatively high; however, the element amounts among 5 manufacturers were different, which could affect the efficacy and toxicity of QSW. All in all, ICP-MS can be used as an effective tool for the analysis of trace elements in QSW and standard quality control needs to be enforced across different manufactures.